Translation Procedures in Subtitle “How Every Child Can Thrive By Five” Video - Hasiyanti Hasiyanti; Ira Maisarah (English Education : English Journal for Teaching and Learning, 2022)
In this research, the researcher concerned on translation study, that is the procedures employed by translator in translating speech video entitled how every child can thrive by five by Molly wright from English into Indonesian. The target from present study was catching up the translation procedures employed by translator. This study used to qualitative method to searched the objective of this study. Then, translation procedures types by Newmark were used by the researcher. The researcher involved herself in gathered data through several steps; watched the speech video, determining, allocating and identifying them entrenched the theory of translation procedures. The finding showed that there were fifth types; literal translation (37%), reduction (4%), deletion (2%), and transposition (41%). The most dominant translation procedure employed in the speech video was transposition.